Design, synthesis, and biological evaluation of a novel series of peripheral-selective noradrenaline reuptake inhibitors – Part 3. Issue 16 (15th August 2016) - Yukawa, Tomoya; Nakada, Yoshihisa; Sakauchi, Nobuki; Kamei, Taku; Yamada, Masami; Ohba, Yusuke; Fujimori, Ikuo; Ueno, Hiroyuki; Takiguchi, Maiko; Kuno, Masako; Kamo, Izumi; Nakagawa, Hideyuki; et al.
Graphical abstract: Abstract: Peripheral-selective inhibition of noradrenaline reuptake is a novel mechanism for the treatment of stress urinary incontinence to overcome adverse effects associated with central action. Here, we describe our medicinal chemistry approach to discover a novel series of highly potent, peripheral-selective, and orally available noradrenaline reuptake inhibitors with a low multidrug resistance protein 1 (MDR1) efflux ratio by cyclization of an amide moiety and introduction of an acidic group. We observed that the MDR1 efflux ratio was correlated with the p K a value of the acidic moiety. The resulting compound9 exhibited favorable PK profiles, probably because of the effect of intramolecular hydrogen bond, which was supported by a its single-crystal structure. The compound9, 1-[(6 S, 7 R )-7-(4-chloro-3-fluorophenyl)-1, 4-oxazepan-6-yl]methyl-2-oxo-1, 2-dihydropyridine-3-carboxylic acid hydrochloride, which exhibited peripheral NET-selective inhibition at tested doses in rats by oral administration, increased urethral resistance in a dose-dependent manner.